2019
DOI: 10.1002/adfm.201900161
|View full text |Cite
|
Sign up to set email alerts
|

Collectively Exhaustive Electrodes Based on Covalent Organic Framework and Antagonistic Co‐Doping for Electroactive Ionic Artificial Muscles

Abstract: In this study, high-performance ionic soft actuators are developed for the first time using collectively exhaustive boron and sulfur co-doped porous carbon electrodes (BS-COF-Cs), derived from thiophene-based boronatelinked covalent organic framework (T-COF) as a template. The one-electron deficiency of boron compared to carbon leads to the generation of hole charge carriers, while sulfur, owing to its high electron density, creates electron carriers in BS-COF-C electrodes. This antagonistic functionality of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 44 publications
1
56
1
Order By: Relevance
“…From Supplementary Table 4 , it is observed that most of the reported bending displacements of ionic soft actuators is measured by taking the thickness in the range of 80–115 µm. The obtained bending displacement of the TP6PP actuator having the thickness of 115 µm is superior to those of other recently reported actuators based on carbonized heteroatom(s) doped carbon materials derived from COFs 26 , 28 or doped graphene 22 , 24 , 27 , 49 , 50 . Likewise, compared with the pure PP actuator, TP5PP and TP4PP actuators respectively showed 220% and 175% enhancements of output displacement for square wave input; and 260% and 190% improvements for sine wave input.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From Supplementary Table 4 , it is observed that most of the reported bending displacements of ionic soft actuators is measured by taking the thickness in the range of 80–115 µm. The obtained bending displacement of the TP6PP actuator having the thickness of 115 µm is superior to those of other recently reported actuators based on carbonized heteroatom(s) doped carbon materials derived from COFs 26 , 28 or doped graphene 22 , 24 , 27 , 49 , 50 . Likewise, compared with the pure PP actuator, TP5PP and TP4PP actuators respectively showed 220% and 175% enhancements of output displacement for square wave input; and 260% and 190% improvements for sine wave input.…”
Section: Resultsmentioning
confidence: 53%
“…Until now, most studies of ionic actuators have focused on one single specific property, while ignoring most others. For example, it has now been well established that heteroatom-doped porous carbon electrodes, because they can provide high electrolyte-accessible surface area and heteroatom-induced superior surface charge capacitance, can play a significant role in the enhancement of actuation performance of an ionic soft actuator 22 , 26 29 . However, porous carbon structures derived mainly from metal organic frameworks (MOFs) and covalent organic frameworks (COFs) have lost their inherent chemical structures during carbonization at temperature higher than 400 °C because of thermal instability.…”
Section: Introductionmentioning
confidence: 99%
“…Applied to actuator COF/PEDOT:PSS [118] 75.2 × 10 3 N-doped carbon/PEDOT:PSS [128] 73.0 × 10 3 graphitic carbon nitride/PVdF [24] 0.38 × 10 3…”
Section: Other Materialsmentioning
confidence: 99%
“…Extensive studies have been carried out to improve the actuation properties of IPMCs. Novel ion‐exchange membrane materials and structures were designed and synthesized to enhance the chemical and mechanical characteristics of IPMCs . For example, Lee et al have reported ion‐exchange membranes based on Nafion/polyimide blends, which can enhance the thermal and mechanical properties, compared to those of traditional Nafion IPMC electromechanical actuators .…”
Section: Introductionmentioning
confidence: 99%